Facebook - Hisrich, Robert D.; Kearney, Claudine ([London] : SAGE, 2016)
This case discusses Mark Zuckerberg and the creation of Facebook. It examines the entrepreneurial mind behind the social media phenomenon and the business strategies that led to its rapid expansion.
Originally Published in: Hisrich, R. D., & Kearney, C. (2013). Scenario: Facebook. Managing innovation and entrepreneurship (pp. 3-6). Los Angeles: SAGE Publications, Inc. ISBN: 9781452241357.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Facebook (Firm); Entrepreneurship -- Case studies